Conspecific and congeneric interactions shape increasing rates of breeding dispersal of northern spotted owls. Issue 7 (11th August 2021) - Jenkins, Julianna M. A.; Lesmeister, Damon B.; Forsman, Eric D.; Dugger, Katie M.; Ackers, Steven H.; Andrews, L. Steven; Gremel, Scott A.; Hollen, Bruce; McCafferty, Chris E.; Pruett, M. Shane; Reid, Janice A.; Sovern, Stan G.; et al.
Abstract: Breeding dispersal, the movement from one breeding territory to another, is rare for philopatric species that evolved within relatively stable environments, such as the old‐growth coniferous forests of the Pacific Northwest. Although dispersal is not inherently maladaptive, the consequences of increased dispersal on population dynamics in populations whose historical dispersal rates are low could be significant, particularly for a declining species. We examined rates and possible causes of breeding dispersal based on a sample of 4, 118 northern spotted owls ( Strix occidentalis caurina ) monitored in seven study areas over 28 yr, 1990–2017, in Oregon and Washington, USA. Using a multistate mark–resight analysis, we investigated the potential impacts of an emergent congeneric competitor (barred owl Strix varia ) and forest alteration (extrinsic factors), and social and individual conditions (intrinsic factors) on 408 successive and 1, 372 nonsuccessive dispersal events between years. The annual probability of breeding dispersal increased for individual owls that had also dispersed in the previous year and decreased for owls on territories with historically high levels of reproduction. Intrinsic factors including pair status, prior reproductive success, and experience at a site, were also associated with breeding dispersal movements. The percent of monitored owls dispersing each year increased from ˜7% early in the study to ˜25% at the end of the study, which coincided with a rapid increase in numbers of invasive and competitively dominant barred owls. We suggest that the results presented here can inform spotted owl conservation efforts as we identify factors contributing to changing rates of demographic parameters including site fidelity and breeding dispersal. Our study further shows that increasing rates of breeding dispersal associated with population declines contribute to population instability and vulnerability of northern spotted owls to extinction, and the prognosis is unlikely to change unless active management interventions are undertaken.